0236 - Masouras, Panicos (My University, 2026)
I serve as the Board Secretary of the Cyprus Computer Society (CCS - www.ccs.org.cy ), the largest ICT professional association in Cyprus. The CCS is an independent, not for profit, non govermental organization and counts more than 1000 ICT professional and scientists as members. The board is elected every two years.I also currently hold the position of the educational activities and training coordinator of the CCS,.